Pendekatan Psikologi dalam Pengobatan Ruqyah Aswaja Masa Pandemi Covid-19 - Eko Purnomo; Aristophan Firdaus; Novita Loka (Faculty of Ushuluddin and Humanities, 2023)
This article discusses the psychological approach in the treatment of ruqyah as a face during the covid 19 pandemic. Ruqyah Aswaja is the treatment of ahlus sunnah wal jama'ah which has been exemplified and explained by the Prophet Muhammad SAW who suffers from illness about what ruqyah practitioners know based on guidance and guidance from Allah SWT. The psychological approach in the treatment of ruqyah aswaja is very useful as a sword of enlightenment and understanding of some Muslim matters, and Islam as a sword of analysis and assessment of several psychological concepts. Ruqyah Aswaja herself in the psychological approach is more accustomed to applying and re-entering the nature and transpersonal. A patient must at least return to his own existence by repenting, returning to fitrah because it is the opening of all circumstances, returning and repenting, then he can find a new path spiritually so that it can trigger good things. This research uses documentation study or literature study. The results of this study are more about how to approach psychology in directing, overcoming and explaining various problems that exist in patients during the covid-19 pandemic.